An adaptive sliding mode control to stabilize wheel slip and improve traction performance - Zirek, Abdulkadir; Voltr, Petr; Lata, Michael; Novák, Jaroslav (SAGE Publications, 2018)
Advanced antislip control methods are available these days. However, due to increasing requirements with regard to demand and emerging technologies in the field of railways, further research on antislip control is required. Therefore, in this study, an antislip control algorithm, based on a sliding mode control, is proposed to stabilize the slip and improve the traction ability of a full-scale tram wheel test stand. To verify the validity of the control scheme, a numerical model of a tram wheel test stand has been generated using the MATLAB editor. The Freibauer and Polach contact theory has been employed to determine the coefficient of adhesion and adhesion force. Moreover, the derived algorithm was implemented on a full-scale tram wheel test stand. Experiments were carried out under several wheel-roller surface conditions. The results of the refined numerical model are in good agreement with the experimental data obtained from the tram wheel test stand. For both the experimental tests and the numerical model, the response of the proposed control algorithm is rather satisfactory with regard to the stabilization of the slip and improvement of the traction ability.
Adaptivní skluzové řízení ke stabilizaci skluzu kola a zlepšení využití trakčního výkonu
Keywords: adhesion; slip; sliding; adaptive; control; adheze; skluz; prokluz; adaptivní; řízení